In Vitro Microropogation Of Sweet Cherry (Prunus Avium L.) Rootstock Cv. ‘mazzard’ (Applied Biological Research, 2011)
The present studies on in vitro propagation of sweet cherry rootstock ‘Mazzard’  was carried out in Biotechnology laboratory, Division of Pomology, Shalimar  during 2006-2009. Surface sterilization of shoot tip explants with 0.1% HgCl2 for  10 minutes yielded maximum aseptic cultures and explant survival. Using explants  from forced stock plant cuttings significantly improved both these parameters.  Maximum explant establishment (76.0%) was observed on MS medium  supplemented with BAP + kinetin (0.25 + 0.25 mg L-1). The established explants  were sub-cultured within 3 to 5 weeks of culture initiation for proliferation  through stimulation of axillary buds. BAP + kinetin (0.25 + 0.25 mg L-1) accounted  for maximum proliferating cultures (99.98%) with highest multiplication efficiency  in terms of proliferation grade (4.0) and shoot number explant-1 (16.2). Rooting  experiments were carried out by incubation of micro-shoots in IBA supplemented  MS media for 10 days under darkness followed by their transfer to hormone-free  MS media with incubation under light conditions of culture room. Micro-shoots  greater than 10 mm in length gave maximum rooting. IBA (2.5 mg L-1) was found  best auxin concentration which not only gave highest rooting (96.66%) but also  maximized root number shoot-1 (6.30) and root length (48.33 mm).
Keywords: Axillary shoot proliferation; in vitro propagation; Mazzard; sweet cherry